2019
DOI: 10.1038/s41586-019-1257-5
|View full text |Cite
|
Sign up to set email alerts
|

Cas13-induced cellular dormancy prevents the rise of CRISPR-resistant bacteriophage

Abstract: Clustered, regularly interspaced, short palindromic repeat (CRISPR) loci of prokaryotes are composed of 30-40 bp repeats separated by equally short sequences of plasmid and bacteriophage origin known as spacers 1 – 3 . Spacers are transcribed and processed into short CRISPR RNAs (crRNAs) that are used as guides by CRISPR-associated (Cas) nucleases to recognize and destroy complementary sequences (known as protospacers) within invaders 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
259
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(268 citation statements)
references
References 30 publications
9
259
0
Order By: Relevance
“…Through this study, we identified two main factors contributing to CasRx-mediated lethality: (i) the catalytic activity of the CasRx HEPN domains, as lethality and tissue necrosis phenotypes were eliminated in dCasRx compared to CasRx crosses, and (ii) the presence of the target transcript resulting in on-target cleavage, as lethality was only observed when crossing Ubiq-CasRxexpressing flies to gRNA GFP -expressing flies. These results recapitulate previous mechanistic analyses of CasRx and other Cas13 ribonucleases, demonstrating that collateral off-target activity following targeted transcript cleavage is a native feature of Cas13 ribonucleases [2,4,[7][8][9]45]. While this feature may not be desirable for generating tools for targeting specific transcripts of genes, this may be useful for generating sensors that get activated in response to a target transcript (e.g.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Through this study, we identified two main factors contributing to CasRx-mediated lethality: (i) the catalytic activity of the CasRx HEPN domains, as lethality and tissue necrosis phenotypes were eliminated in dCasRx compared to CasRx crosses, and (ii) the presence of the target transcript resulting in on-target cleavage, as lethality was only observed when crossing Ubiq-CasRxexpressing flies to gRNA GFP -expressing flies. These results recapitulate previous mechanistic analyses of CasRx and other Cas13 ribonucleases, demonstrating that collateral off-target activity following targeted transcript cleavage is a native feature of Cas13 ribonucleases [2,4,[7][8][9]45]. While this feature may not be desirable for generating tools for targeting specific transcripts of genes, this may be useful for generating sensors that get activated in response to a target transcript (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, RNA targeting was demonstrated with ubiquitous, inducible and tissue specific CasRx expression systems against native and synthetic RNA targets, which are prerequisites for enabling comprehensive studies of gene function. However, we did also consistently observe both cellular toxicity from the ubiquitous expression of CasRx and dCasRx as we could not generate homozygous strains for either, and unexpected lethality and tissue necrosis, presumably due collateral off target effects which have been a feature previously observed for many CRISPR ribonucleases including CasRx [2,4,[7][8][9]45]. Nevertheless, in both bidirectional and Gal4/UAS crosses, we were able to obtain visible phenotypes as well as quantitative evidence (e.g., RNAseq data demonstrating a reduction in target gene expression) indicating that the CasRx is capable of targeting and degrading target RNA in flies.…”
Section: Discussionmentioning
confidence: 50%
“…In CRISPR-Cas systems like type III and type VI, Cas nucleases can be activated for nonspecific cleavage of RNA (Hille et al 2018). Perhaps, this is a means to prevent phage proliferation by initiating programmed cell death (PCD), abortive infection or dormancy in order to save the bacterial population (Koonin and Zhang 2017;Meeske, Nakandakari-Higa, and Marraffini 2019). Further studies are required to investigate the cost-benefit relation of such nonspecific activities of Cas12a to the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cOA activated, non-specific ribonucleases described above for type III systems, type VI (Cas13) effectors provide effective immunity against mobile genetic elements by degrading RNA non-specifically 32,33 . The mechanism for this immunity was recently shown to result in degradation of host, rather than virus, RNA, driving infected cells into dormancy and thus preventing the spread of infection 34 . DNA is also a target for collateral degradation.…”
Section: Function Of Can1 In Vivomentioning
confidence: 99%